Impact of Marital Status on the Outcome of Acute Coronary Syndrome: Results From the Acute Coronary Syndrome Israeli Survey. Issue 14 (16th July 2019) - Marcus, Gil; Litovchik, Ilya; Pereg, David; Beigel, Roy; Sholmo, Nir; Iakobishvili, Zaza; Goldenberg, Ilan; Fuchs, Shmuel; Minha, Sa'ar
Abstract : Background: Marriage is one of the common forms of social support. Conflicting evidence exists about the impact of marital status on the outcomes of patients with acute coronary syndrome (ACS). It is further not clear if sex disparity exists in the outcome of married and nonmarried patients with ACS. Methods and Results: Data from the ACS Israeli Survey, collected between 2004 and 2016, were used to compare baseline characteristics, clinical indexes, and outcomes of married and nonmarried patients with ACS. Cox regression analysis and propensity score matching were used to explore if marital status was independently associated with long‐term outcome. Of 7233 patients included with reported marital status, 5643 (78%) were married. Married patients were younger (62.69±12.07 versus 68.47±14.84 years; P <0.001), more frequently men (83.1% versus 54.8%; P <0.001), and less likely to be hypertensive (61.1% versus 69.3%; P <0.001). All‐cause mortality incidence at 30 days and at 1 year was lower in married patients (3.1% versus 7.6% [ P <0.001]; and 7.1% versus 15.3% [ P <0.001], respectively). After adjusting for multiple covariates, the hazard ratio for 5‐year all‐cause mortality for married patients was 0.74 (95% CI, 0.62–0.88). Similar results were observed after propensity score matching. Kaplan‐Meier estimates for all‐cause mortality at 5 years demonstrated the best prognosis for married men and the worst for nonmarried women. Conclusions: Marriage is independently associated with better short‐ and long‐term outcomes across the spectrum of ACS. Attempts to intensify secondary prevention measures should focus on nonmarried patients and especially nonmarried women.